2019
DOI: 10.1177/1468018119827475
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and health: An empirical investigation

Abstract: This article empirically examines the impact of globalization on the health status of countries by using panel data. Unlike previous studies, it has attempted to use three different dimensions of globalization and estimate their impact on health status measured by infant mortality rate and life expectancy. It also introduces an initial level of development status as an explanatory variable and found that it has an important role. The fixed effects panel data analysis shows that globalization has a positive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…More specifically, Tausch [ 93 ] suggested that globalization only improves healthcare status for underdeveloped countries, which could explain our results referred to European (not underdeveloped) countries and the relative unimportance of globalization in terms of health improvement. In the same vein, the authors of [ 91 , 94 , 133 ] pointed out that the positive association between globalization and a healthier population would be limited to developing countries. In this regard, this positive relationship between globalization and health in the least developed countries can be explained by increasing the easy supply of life-saving drugs, improving the institutional features of an economy which may influence the lifestyles of masses and enhancing the use of friendly-environment methods of production by firms [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, Tausch [ 93 ] suggested that globalization only improves healthcare status for underdeveloped countries, which could explain our results referred to European (not underdeveloped) countries and the relative unimportance of globalization in terms of health improvement. In the same vein, the authors of [ 91 , 94 , 133 ] pointed out that the positive association between globalization and a healthier population would be limited to developing countries. In this regard, this positive relationship between globalization and health in the least developed countries can be explained by increasing the easy supply of life-saving drugs, improving the institutional features of an economy which may influence the lifestyles of masses and enhancing the use of friendly-environment methods of production by firms [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important characteristic of this index is the fact that it offers an individualized image of the impact of globalization, omitting any reference to transactions, trade flows or economic linkages which occur internally within the borders of each country. Previous empirical research suggests a positive association between globalization and a healthier population in developing countries [ 28 , 91 , 92 , 93 , 94 ] whilst other works conclude that there is no relationship between both variables [ 88 , 89 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globalization appears to improve population health outcomes such as infant mortality rate (IMR) and life expectancy (LE) regardless of a country’s level of development (i.e., developed, developing, or underdeveloped) [ 27 , 28 ]. Links between the dimensions of globalization (i.e., social, political, and economic) and general population health are less clear cut [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Links between the dimensions of globalization (i.e., social, political, and economic) and general population health are less clear cut [ 29 ]. For less developed countries, the economic dimension of globalization appears to provide the strongest determinant in IMR and LE, whereas for more developed countries, the social aspect of globalization is the strongest factor [ 27 ]. This suggests that as a country becomes more economically stable, it then moves towards greater social and political integration into global society; and for less developed countries, increased wealth creation through economic integration potentially delivers the greatest increases in population health.…”
Section: Introductionmentioning
confidence: 99%